Catalytic Hydrogenation of Post-Mature Hydrocarbon Source Rocks Under Deep-Derived Fluids: An Example of Early Cambrian Yurtus Formation, Tarim Basin, NW China - Xiaowei, Huang; Zhijun, Jin; Quanyou, Liu; Qingqiang, Meng; Dongya, Zhu; Jiayi, Liu; Jinzhong, Liu (Frontiers in Earth Science, 2021)
As a link between the internal and external basin, the deep derived fluids play a key role during the processes of hydrocarbon (HC) formation and accumulation in the form of organic-inorganic interaction. Two questions remain to be answered: How do deep-derived fluids affect HC generation in source rocks by carrying a large amount of matter and energy, especially in post-mature source rocks with weak HC generation capability? Can hydrogen and catalysts from deep sources significantly increase the HC generation potential of the source rock? In this study, we selected the post-mature kerogen samples of the early Cambrian Yurtus Formation in the Tarim Basin of China. Under the catalytic environment of ZnCl2 and MoS2, closed system gold tube thermal simulation experiments were conducted to quantitatively verify the contribution of catalytic hydrogenation to "HC promotion" by adding H2. The catalytic hydrogenation increased the kerogen HC generation capacity by 1.4–2.1 times. The catalytic hydrogenation intensity reaction increased with temperature. The drying coefficient of the generated gas decreased significantly as the increasing yield of heavy HC gas. In the simulation experiment, alkane δ13C becomes lighter after the catalytic hydrogenation experiment, while δ13CCO2 becomes heavier. In the process of catalytic hydrogenation, the number of gaseous products catalyzed by ZnCl2 is higher than that catalyzed by MoS2 under the same conditions, indicating that ZnCl2 is a better catalyst for the generation of gaseous yield. Meanwhile, Fischer-Tropsch synthesis (FFT) reaction was happened in the catalytic hydrogenation process. The simulation experiment demonstrates that hydrogen-rich components and metal elements in deep-derived fluids have significant catalytic hydrogenation effects on organic-rich matter, which improved the HC generation efficiency of post-mature source rocks.